Revisiting 'social tectonics': The middle classes and social mix in gentrifying neighbourhoods. (October 2015) - Jackson, Emma; Butler, Tim
Studies of gentrification in London have shown that some groups of middle-class people have been attracted to poor and multi-ethnic areas of inner London in part because of their social and ethnic mix. However, the attraction has often not translated into everyday interaction. In an earlier account of gentrification in Brixton this de facto social segregation was typified as a process of 'social tectonics'. In this paper we compare two ethnically and socially mixed neighbourhoods, Peckham and Brixton, that at different times have represented the 'front line' of gentrification in London. We examine the extent to which the gentrification of Brixton in the late 1990s is being mirrored by the gentrification that is occurring today in Peckham – a similarly mixed and counter-cultural area of South London. Whilst we identify continuities between the gentrification process in these two areas separated by a decade of boom and recession, we suggest that the Peckham example demonstrates the need for a more developed approach to the issue of social mixing than that implied by the social tectonics metaphor. Specifically, we argue that there is a need to explain how the presence of classed and ethnic 'others' can be central to the formation of identities within some middle-class fractions in such enclaves in the inner city, and how attitudes and neighbourhood practices can change over time.